2010
DOI: 10.1071/wf07131
|View full text |Cite
|
Sign up to set email alerts
|

The wildland - urban interface fire problem - current approaches and research needs

Abstract: Wildfires that spread into wildland–urban interface (WUI) communities present significant challenges on several fronts. In the United States, the WUI accounts for a significant portion of wildland fire suppression and wildland fuel treatment costs. Methods to reduce structure losses are focussed on fuel treatments in either wildland fuels or residential fuels. There is a need for a well-characterised, systematic testing of these approaches across a range of community and structure types and fire conditions. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
249
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(256 citation statements)
references
References 18 publications
3
249
0
4
Order By: Relevance
“…Knowledge for estimating and mitigating risk from wildfires is most critical at the wildland urban interface (WUI): the boundary between flammable vegetation and the houses and other assets in the urban land (Safford et al, 2009;Mell et al, 2010). As urban populations expand, so do the number of houses in the WUI in Australia (Hughes and Mercer, 2009) and in the USA (Schoennagel et al, 2009), and house losses increase accordingly (Schoennagel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge for estimating and mitigating risk from wildfires is most critical at the wildland urban interface (WUI): the boundary between flammable vegetation and the houses and other assets in the urban land (Safford et al, 2009;Mell et al, 2010). As urban populations expand, so do the number of houses in the WUI in Australia (Hughes and Mercer, 2009) and in the USA (Schoennagel et al, 2009), and house losses increase accordingly (Schoennagel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive urban growth in SoCal significantly increases the wildland-urban interface, and thus seriously compounds wildfire hazards, resulting in loss of human life and property [1,2]. Thus, improving fire danger assessment systems with a high spatial resolution and a wide coverage across the vast wildland is essential for decision makers and fire agencies to develop and implement pro-active policies.…”
Section: Introductionmentioning
confidence: 99%
“…Our novel approach is to test the LFM relationship with enhanced vegetation index (EVI) that is averaged over various spatial extents centered at each in-situ LFM sampling location. The objectives of this study are to: (1) Compare seasonal and interannual characteristics of LFM with those of VIs calculated from satellite data in SoCal; (2) develop an empirical model function of LFM based on an optimal vegetation index together with temperature data; and, (3) evaluate the feasibility, as well as limitations of the empirical model for wildfire danger assessments.…”
Section: Introductionmentioning
confidence: 99%
“…The fire impact may be at various intensity levels and may include convective heating or direct contact of the flames, radiant heat flux from nearby flames and airborne firebrands (Cohen 2000;Koo et al 2010;Mell et al 2010). Focusing on the effect of meteorology on fire characteristics, Blanchi et al (2010) analysed the relationship between house loss and the fire weather under which it occurred and found that virtually all of the losses occurred under extreme conditions.…”
Section: Introductionmentioning
confidence: 99%